(3GdeHGMK GdeTQbjIs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3jHOC HGdLedI GdKGfjI ai Gd LhGgQ hajgG afhf fcJg (B( (3GdLedI GdKGfjI ai GdLhGgQ hajgG afhf KdGKI Gdaf GdChd ai GdCLSGe hajg CQHYI GHhGH GdHGH GdChd ai LhgQ GdCLSGe hajg KeGfjI YTQ aUdkG s
(3BNQgG (B:s
(3adgPG UGQ GdEfSGf MOKkG HGdWHY adfNJe GdcJGH MGeOjf ddg JYGdi hGddg CYde HGdUhGH s
(3GdKdK GdKGdKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
Keywords: (3GdadSaI hGdefWbs